2017
DOI: 10.1186/s12904-017-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Existential decision-making in a fatal progressive disease: how much do legal and medical frameworks matter?

Abstract: BackgroundHealthcare legislation in European countries is similar in many respects. Most importantly, the framework of informed consent determines that physicians have the duty to provide detailed information about available therapeutic options and that patients have the right to refuse measures that contradict their personal values. However, when it comes to end-of-life decision-making a number of differences exist in the more specific regulations of individual countries. These differences and how they might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Regulations differ from one country to another, and such differences may affect the patient's choices. In general, the principle of autonomy dictates that physicians have the duty to provide detailed information on the available therapeutic options and that patients have the right to refuse measures that go against their personal values [27].…”
Section: How To Prioritize Patient Preferences?mentioning
confidence: 99%
See 2 more Smart Citations
“…Regulations differ from one country to another, and such differences may affect the patient's choices. In general, the principle of autonomy dictates that physicians have the duty to provide detailed information on the available therapeutic options and that patients have the right to refuse measures that go against their personal values [27].…”
Section: How To Prioritize Patient Preferences?mentioning
confidence: 99%
“…A study mentions three distinct situations involving bioethical problems in existential decision-making: the first situation concerns the ethical responsibility of informing patients about the available treatment options and future implications of the diagnosis; the second situation concerns the retention or implementation of long-term supportive therapies without therapeutic utility; and the third situation relates to the continuation or discontinuation of measures that sustain life in different cases. In some countries, there is a fourth option, which is of hastening death through the application of active drugs [27].…”
Section: How To Prioritize Patient Preferences?mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that age, gender, religion, and geographic region are associated with willingness to forgo life-sustaining treatments [1921]. The influence of geographic region is likely because attitudes and legal settings regarding end-of-life decision-making vary within Europe [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the ventilator is itself rather inexpensive, the economic, social and emotional burdens of 24/7 care are challenging both to formal and informal caregivers [7]. The use of TIV in ALS varies ranging from 0% of patients from the UK, 1-14% in the USA, 3% in Germany, 2-5% in France, 11% in northern Italy, to 27-45% in Japan, likely reflecting cultural, economic, legal and organisational differences both within and outside the healthcare system [8,9]. In Norway and Sweden, 6.7% of men and 3.8% of women living with ALS between 2002 and 2007 used TIV, suggesting that gender may also influence preferences or access to such treatment [10].…”
Section: Introductionmentioning
confidence: 99%